2016
DOI: 10.14238/sp16.2.2014.86-90
|View full text |Cite
|
Sign up to set email alerts
|

Penilaian Kualitas Hidup pada Anak dengan Penyakit Jantung Bawaan Asianosis dan Sianosis

Abstract: Latar belakang. Setiap tahun seribu bayi lahir dengan penyakit jantung bawaan (PJB). Terapi bertujuan mengurangi gejala klinis, mencegah gagal jantung, penutupan defek, dan meningkatkan kualitas hidup. Evaluasi terhadap kualitas hidup menjadi penting karena dengan tata laksana yang baik sekarang ini, anak dengan PJB memiliki harapan hidup yang lebih lama.Tujuan. Menilai perbedaan kualitas hidup anak penderita PJB asianosis dengan sianosis.Metode. Penelitian menggunakan studi potong lintang telah dilakukan dari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Consistent with the previous study on the developmental outcome of children with CHD, our study also found that nutritional problem [3], [10], [15], cognitive delay [3], [5], [9], and lower quality of life [8], [14] are common problems in CHD children [10]. In nutritional assessment, both groups showed the same proportion of severely underweight 50.0%.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with the previous study on the developmental outcome of children with CHD, our study also found that nutritional problem [3], [10], [15], cognitive delay [3], [5], [9], and lower quality of life [8], [14] are common problems in CHD children [10]. In nutritional assessment, both groups showed the same proportion of severely underweight 50.0%.…”
Section: Discussionsupporting
confidence: 91%
“…It also appropriates with a study in Cairo which found that malnutrition, stunting, and wasting proportion were significantly higher among cyanotics (62.8%, 74.4%, and 25.6%) compared with acyanotics (49.5%, 63.3%, and 18.3%) [12]. In addition, cyanotic heart defect was known to have a correlation with the decrement of insulin growth factor-1 level (r = 0.402, p < 0.05) [14], which is in agreement with Eren et al who stated chronic hypoxia had a negative effect on nutrition and growth hormone, by decreasing insulin growth factor-1 (somatomedin) level that is produced in the liver and regulated by the binding of growth hormone to growth hormone receptors. These findings indicated that chronic hypoxemia might serve as the underlying cause by decreasing the production of insulin growth factor-1 which induced growth failure in patients with cyanotic CHD [11], [16], [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations